Determinant of students' cognitive achievement in senoir secondary school physics: how important is test response mode? (2006)
In this paper, the authors, using the ex-post -factor procedure, examine the effect of test response mode (essay and objective tests) on students' scholastic achievement in physics at the senior secondary school level. The sample consisted of 475 SSII students(233 males and 242 females) drawn from seven randomly selected senior secondary schools in Ibadan south east local government area of Oyo state. Data analysis was done using mean scores and t-test (paired and independent sample). Results showed that: students performed better in objective test than in essay test. There was no significant difference in the performance of male and female students in the objective test. Male students performed better than female students in essay test. The authors offered suggestions on what physics teacher could do to help students achieve better results in physics essay tests and sustain thier interest in physics, and more importantly improve their overall performance in physics